PEMBERDAYAAN PELAJAR SEKOLAH MENENGAH ATAS (SMA) MELALUI KEGIATAN RELAWAN MAHASISWA LOKAL DAN ASING DALAM MENINGKATKAN KEMAMPUAN BERBAHASA INGGRIS SISWA - Agung Setiawan; Ella Izzatin Nada; M Rikza Chamami; Erna Wijayanti (Buletin Abdi Masyarakat, 2021)
Volunteering project is a social activity which has been done by youth in developing human resources in ‎their environment. It is a teaching activity that volunteers can teach  in school, that is Senior High School (SMA) ‎Theresiana Semarang. There are two kinds of class in this school, they are reular and imerci class which students in ‎imerci class understand and fluence in speaking English. This volunteering project uses teaching method such ‎conversation and public speaking. The aim of the activity is to help the students in developing their speaking ability ‎so that they can communicate using English. Hopefully, the students can speak fluently using English as their ‎provision in facing defiance of the globalization era whereas the competition of the human resources is increasingly ‎high.‎Keywords: Volunteers, Empowerment, Students, Local, Foreign